Caso de estudio: análisis de los efectos del desarrollo financiero en el crecimiento económico de mercados emergentes: caso peruano y chileno - Alonso Masgo, Carlos Alberto (2022)
The financial system fulfills the function of resource allocation in an economy, hence the importance of its development for economic growth. This study aims to establish the determinants of financial development and its effects on economic growth for the case of Peru and, comparatively, for the case of Chile. Regarding the methodology used, the panel data econometric analysis method is applied, taking as explanatory variables of economic growth, determinants of financial development, Credit to the Private Sector, Number of Financial Offices, number of Correspondent ATMs, number of Automatic ATMs, Deposits, Market Capitalization and, in a complementary manner, Commercial Opening. Among the main findings, the variables selected as determinants of financial development turn out to be significant with a positive effect on economic growth. Finally, the corresponding recommendations are made in order to improve the implication of the selected variables in economic growth within the opportunities for improvement observed.